(untitled) (Bulletin KNOB, 2022)
The new, enlarged premises for the Tweede Kamer (Lower House) took shape between 1970 and 1992. The key issue was how to integrate this huge complex with the historic Binnenhof. This article describes the design process, the underlying ideas, and the outcome. In 1975 an open architectural competition was organized for the building’s design. The task was to house the Tweede Kamer in accordance with a detailed brief and to insert the resulting complex with utmost sensitivity into the Binnenhof heritage site. The jury concluded that none of the submitted designs met these requirements. OMA’s design did, however, spark debate. It broke open the buildings around the Binnenhof and placed the new-build next to the thirteenth-century Ridderzaal (Knights’ Hall). The sheer radicality of the intervention appalled the jury. In the wake of the failed competition, three architects were invited to submit designs. Once again, the designs were deemed unsatisfactory, and the parameters were revised. The panel of judges felt Pi de Bruijn had best understood the nature of the task. In 1980 he was appointed architect. Crucial to the eventual outcome was a recommendation from the Rijksdienst voor de Monumentenzorg (Government Department for the Preservation of Historic Buildings) to the effect that the urban design structure should be meticulously preserved. The newbuild shouldonly be visible on Het Plein and on the Hofplaats-Lange Poten corner. A major consideration was how to conjure a coherent parliament building out of the mix of old and new. De Bruijn strove for clarity and legibility. He conceived the new section as both a central hall in the Tweede Kamer and a public passagewayin the city: a public route as an expression of the transparency and proximity of the parliament vis-á-vis citizens. Architecturally he aimed for an impression of calm and a clearly laid-out hall that would radiate unity and coherence. In the materialization this was achieved through the use of granite for the floors and the internal and external elevations. Even before the opening, the Chairman of the Parliament had decided against making the building publicly accessible; the central hall became part of the interior. The ambition to make the Tweede Kamer open and accessible came to naught and from the outside the complex looked like an impenetrable fortress. The question of what constituted a dignified centre of government and what architectural expression that entailed was never posed. Instead, the focus was on functionality, integration with the heritage context, connecting old and new, rendering the business of politics visible and striving for simplicity and calm. This manifested as a taut new-build volume slotted in between the existing buildings. Against the simplicity of the grand gesture, there is the disorderly connection with which the new building lands on the anything but simple and unambiguous converse of the surrounding historical buildings.